Teachers as Murabbi: An Analysis of the Teacher's Role in Character Formation from the Perspective of Islamic Educational Philosophy at SD Persatuan Islam Karawang - Muzaki, Iqbal Amar; Nurhasan; Faizin, Muhamad; Agus Susilo Saefullah; Abdul Hakim; Mohd.Sobri bin Ellias (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study addresses the urgent concern in contemporary education regarding the weakening of student character due to the influence of external cultures and the growing tide of modernity that misaligns with Islamic values. In this context, the role of the murabbi becomes pivotal. The aim of this research is to analyze how teachers at SD Persatuan Islam (Persis) Karawang implement their role as murabbi in shaping students’ character based on Islamic educational philosophy. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis involving homeroom teachers, Islamic religious education teachers, principals, and purposively selected students. The data were analyzed using the Miles and Huberman model and verified through triangulation and credibility measures. The findings reveal that teachers consistently integrate Islamic values into the learning process and school life through exemplary conduct, value habituation, and spiritual mentoring. In conclusion, the holistic implementation of the murabbi role proves effective in fostering Islamic character among students and offers a replicable model for Islamic-based character education at the elementary level. This study contributes by offering a conceptual framework of the murabbi role rooted in Islamic educational philosophy and grounded in empirical findings from elementary school settings.